The role of Dissemination of Monitoring and Evaluation Results in the promotion of Performance of Digital Education Technology Project In Malawi - Winiko, Symon Manyenje (IJRDO- Journal of Educational Research, 2018)
The study aimed to investigate the influence of Dissemination of Monitoring and Evaluation Results on the performance of Digital Education Technology (DET) project in Malawi. Methodologically the study was guided by descriptive survey correlational design. The target population was comprised of 456 persons who were involved in the management, implementation and Monitoring and Evaluation of the DET project. 204 respondents were sampled using proportionate stratified random sampling approach to ensure that all categories of respondents were represented in the sample. A table of random numbers was used to sample participants from each stratum. Questionnaire and interview guide were utilized as data collection instruments. These instruments were piloted to enhance validity and reliability. Quantitative data analysis was done using SPSS and both descriptive and inferential statistical analysis techniques were used. Frequency, mean and standard deviation were utilized as descriptive statistics while Pearson product moment correlational coefficient and regression analysis were used as inferential statistical tests. The qualitative data was analyzed using thematic analysis and this involved the identification of recurrent themes from the voices of the participants. With r=0.367, r2=0.135, F (1, 183) =28.309 at p=0.001<0.05 the study has established that Dissemination of Monitoring and Evaluation results has a moderate positive influence on performance of DET project in Malawi. The study recommends the strengthening of Dissemination of M&E results in order to improve the performance of DET project.